New insights on the stratigraphy of Tobruq-Burdi area- Marmarica, NE Libya - Muftah, Ahmed M.; El Ebaidi, Saad K.; Al Mahmoudi, Anas; Faraj, Faraj H.; Khameiss, Belkasim (Libyan Journal of Science &Technology, 2022)
The stratigraphy of the Marmarica region in the eastern region of Libya (called Tobruq-Burdi), the nomenclature contradiction in stratigraphy has been reviewed. Three surface exposures, Wadi al Hash, Wadi al Shaigh at Tobruq area and Wadi al Rahibat Burdi area have been measured, sampled and analyzed using both the lithology and the fossil assemblages. Previous works in the area have been revised to sort out the contradiction on the stratigraphy. A disconformity surface with different time interval have been documented at two localities. The first location is a well-known transgressive event (i.e. glauconitic bed) which was recognized at the basal part of the Oligo-Miocene Al Faidiyah Formation delineating the disconformity surface separating the Oligo-Miocene Al Faidiyah Formation from the underlying Middle Eocene Darnah Formation at Wadi al Hash and Wadi Al Shaigh sections. However, the second location exhibits an angular unconformity surface separating the Lower Oligocene algal limestone of Al Bayda Formation from the underneath Campanian Al Majahir Formation at Wadi al Rahib section in Burdi area. Meanwhile, the upper two formations the Oligo-Miocene Al Faidiyah Formation and the overlying Middle Miocene Al Gaghbub Formation in the study area are separated from each other by disconformity of short interval time. The area was tectonically stable with extensive spatial distribution with some thickness variation in response to the paleorelief of the area of study. On the basis of foraminiferal assemblages, the Darnah Formation is Middle Eocene, Al Faidiyah Formation is Late Oligocene, Al Gaghbub Formation is Middle Miocene at Tobruq and Burdi area. The term Al Khowaymat Formation is replaced by Darnah Formation for (the Lower Member of the so-called Al Kowaymat) and Al Faidiyah Formation for (the Upper Member of the so-called Al Kowaymat) at the studied sections in Tobruq area. Similarly, the term Lower Member of Al Khowaymat Formation is replaced by Al Majahir Formation at Wadi al Rahib section in the Burdi area.